Penerapan Aplikasi Pelaporan Orang Asing (APOA) Dalam Pemantauan Keberadaan Orang Asing - Adinda Anderson; Aldri Frinaldi (Jurnal Teori dan Riset Administrasi Publik, 2019)
This study aimed to determine the Implementation of Foreign Reporting Applications (APOA) at the Working Area of the Immigration Office Class I in Padang. APOA was an online application that aims to facilitate the reporting process of foreigners by reporters and for Immigration Officers. This application was used as data and information in the supervision of foreigners. This research is a qualitative research with descriptive method. Research informants were selected through purposive sampling. Data in this study were collected trough interview, observation, and documentation study. The data were validated through triangulation method. Then the data were analyzed with interactive model analysis. The results of this research showed that the implementation of the Foreign Reporting Application (APOA) in monitoring the presence of foreigners in the Working Area of the Class I Immigration Office in Padang had not proceeded properly because there were still obstacles which caused APOA not to be carried out in accordance with its objectives.